2019
DOI: 10.1002/mc.22961
|View full text |Cite
|
Sign up to set email alerts
|

cd44 deletion suppresses atypia in the precancerous mouse testis

Abstract: Loss‐of‐function of RHAMM causes hypofertility and testicular atrophy in young mice, followed by germ cell neoplasia in situ (GCNIS) of the testis, cellular atypia, and development of the testicular germ cell tumor (TGCT) seminoma. These pathologies reflect the risk factors and phenotypes that precede seminoma development in humans and—given the high prevalence of RHAMM downregulation in human seminoma—link RHAMM dysfunction with the aetiology of male hypofertility and GCNIS‐related TGCTs. The initiating event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…Likewise, the ductular proliferation (Figures 2-4) and liver size (Figure 1a) were unaffected by Cd44 loss. In contrast to our study, previous reports demonstrated that deletion of the Cd44 gene inhibits initiation of colon carcinoma in Apc(Min/+) mice [61] and oncogenic progression in the testis of RHAMM-deficient mice [62]. Thus, our results suggest that deletion of Nf2 may specifically release tumorpromoting mechanisms that are independent of CD44; or alternatively, CD44 function is compensated by other molecules in Cd44-deficient Nf2-mutant mice.…”
Section: Icam-1 May Overtake Cd44 Function As a Coreceptor Of Recepto...contrasting
confidence: 99%
“…Likewise, the ductular proliferation (Figures 2-4) and liver size (Figure 1a) were unaffected by Cd44 loss. In contrast to our study, previous reports demonstrated that deletion of the Cd44 gene inhibits initiation of colon carcinoma in Apc(Min/+) mice [61] and oncogenic progression in the testis of RHAMM-deficient mice [62]. Thus, our results suggest that deletion of Nf2 may specifically release tumorpromoting mechanisms that are independent of CD44; or alternatively, CD44 function is compensated by other molecules in Cd44-deficient Nf2-mutant mice.…”
Section: Icam-1 May Overtake Cd44 Function As a Coreceptor Of Recepto...contrasting
confidence: 99%
“…It has been shown that CD44 is not expressed in normal testes but only in a subset of GCNIS testes and its genetic deletion in the RHAMM truncation background markedly reduces the percentage of mice presenting with germ cell atypia. It is suggested that overexpression of CD44 combined with RHAMM dysfunction drives oncogenesis in the testis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[24,[83][84][85][86] Nevertheless, several experimental studies predict that, like CD44, RHAMM can also act as a tumor suppressor in specific contexts. This possibility was first suggested by evidence associating reduced expression or gene dosage of RHAMM with initiation of both seminomas [87] and malignant peripheral nerve sheath tumors, [88] and by experimental evidence that loss of Rhamm exons 10-18 promotes seminoma induction. [89] Furthermore, the progression of pancreatic tumors to metastasis is increased rather than decreased in Rhamm −/− mice [72] that are crossed to transgenic mouse models of pancreatic cancer susceptibility.…”
Section: Rhamm/hmmrmentioning
confidence: 99%